A risk score system for stratifying the risk of relapse in B cell acute lymphocytic leukemia patients after allogenic stem cell transplantation. Issue 10 (20th May 2021) - Cao, Le-Qing; Zhou, Yang; Liu, Yan-Rong; Xu, Lan-Ping; Zhang, Xiao-Hui; Wang, Yu; Chen, Huan; Chen, Yu-Hong; Wang, Feng-Rong; Han, Wei; Sun, Yu-Qian; Yan, Chen-Hua; et al.
Abstract: Background: For patients with B cell acute lymphocytic leukemia (B-ALL) who underwent allogeneic stem cell transplantation (allo-SCT), many variables have been demonstrated to be associated with leukemia relapse. In this study, we attempted to establish a risk score system to predict transplant outcomes more precisely in patients with B-ALL after allo-SCT. Methods: A total of 477 patients with B-ALL who underwent allo-SCT at Peking University People's Hospital from December 2010 to December 2015 were enrolled in this retrospective study. We aimed to evaluate the factors associated with transplant outcomes after allo-SCT, and establish a risk score to identify patients with different probabilities of relapse. The univariate and multivariate analyses were performed with the Cox proportional hazards model with time-dependent variables. Results: All patients achieved neutrophil engraftment, and 95.4% of patients achieved platelet engraftment. The 5-year cumulative incidence of relapse (CIR), overall survival (OS), leukemia-free survival (LFS), and non-relapse mortality were 20.7%, 70.4%, 65.6%, and 13.9%, respectively. Multivariate analysis showed that patients with positive post-transplantation minimal residual disease (MRD), transplanted beyond the first complete remission (≥CR2), and without chronic graft-versus-host disease (cGVHD) had higher CIR ( P < 0.001, P = 0.004, and P < 0.001, respectively) and worse LFS ( P < 0.001, P = 0.017, and P < 0.001, respectively), and OS ( P < 0.001, P = 0.009, and P < 0.001, respectively) than patients without MRD after transplantation, transplanted in CR1, and with cGVHD. A risk score for predicting relapse was formulated with the three above variables. The 5-year relapse rates were 6.3%, 16.6%, 55.9%, and 81.8% for patients with scores of 0, 1, 2, and 3 ( P < 0.001), respectively, while the 5-year LFS and OS values decreased with increasing risk score. Conclusion: This new risk score system might stratify patients with different risks of relapse, which could guide treatment.